EFFORTS TO OPTIMIZE HEALTH SERVICES FOR ELDERLY PRISONERS AT TULUNGAGUNG CLASS IIB CORRECTIONAL INSTITUTION - Dimas Aditiya Pratama; Budi Priyatmono; Ali Muhammad; Umar Anwar (Universitas Nusa Cendana, 2026)
The elderly inmate population at Class IIB Correctional Facility (Lapas) in Tulungagung continues to grow, demanding the optimization of adaptive and comprehensive healthcare services. This study aims to analyze efforts to optimize healthcare services, identify key challenges, and formulate innovative solutions to fulfill the basic rights of elderly inmates. A qualitative descriptive method was employed, utilizing in-depth interviews with correctional officers, medical personnel, and elderly inmates. The findings reveal that efforts to optimize healthcare services have been implemented through regular medical visits, designated housing blocks for elderly inmates, the application of specialized Standard Operating Procedures (Dilan and Milia), and collaborations with the local Health Office and referral hospitals. However, several major obstacles persist, including a limited number of medical personnel (only one doctor and one nurse for the entire inmate population), restricted availability of medications, inadequate elderly-friendly facilities, and a manual medical record system. Family involvement also plays a significant role in accelerating the recovery process of elderly inmates. This study further recommends an innovative initiative called SEKOCI (Rapid Response Health System for Elderly Inmates), aimed at enhancing emergency healthcare response through the installation of emergency buttons in elderly housing blocks. Other strategic recommendations include increasing human resources, digitalizing health records, and strengthening multi-sectoral collaboration. The results of this research are expected to serve as a reference for correctional policy, ensuring that healthcare service optimization for elderly inmates aligns with the principles of justice, humanism, and accountability. Keywords: Inmate Characteristics; Narcotics Inmates; Deviant Behavior